Pengembangan Media Pembelajaran Fisika Projectile Launcher sebagai Alat Praktikum Fisika pada Materi Gerak Parabola Fisika Kelas XI IPA - Riki Chandra Wijaya; Damris M; Kamid Kamid (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
Parabolic motion is one of the teaching materials studied by senior high school students where they are commonly tough through conventional teaching. The objectives of this study were to develop a projectile launcher to help students studying parabolic motion. A development model of Richey,dkk was adopted in this study. The product was validated by experts and used in a small group of students. It was then used in a real classroom teaching in which the projectile launcher was used and maximum stance were measured. The theoretical calculation and measured stance were compared to show the student the usefulness of the product. The result showed that the projectile launcher developed in this study can be used for of parabolic motion study and improve student achievement.